Peutz Jeghers Syndrome in 47 Years Old Woman (Histopathological Review) : Case Report - Danu Yuliarto; Prasetyadi Mawardi; Ambar Mudigdo (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Peutz-Jeghers syndrome (PJS) is an autosomal dominant inherited disorder, characterizedby intestinal hamartoma polyps in association with distinct patterns of skin and mucosal macular melanindeposition. Patients with PJS have a 15-fold increased risk of developing bowel cancer compared to thegeneral population.Case: A 47-year-old woman complained of black patches appearing on the lower and upper lips. Severalmonths ago, the patient said that black patches appeared on the gums and inner cheeks. Gastrointestinalcomplaints such as nausea or vomiting were previously denied. Dermatological examination in the oriset ginggiva et buccalis region showed multiple well-defined hyperpigmented macules. Histopathologicalexamination found an increase of melanocytes in the stratum basale with rows of melanocytes. Patienthad an endoscopy in the gastrointestinal tract and histopathological examination of the colonic mucosa, noabnormalities were found and no signs of malignancy were found on histopathological examination.Conclusion: Result of histopathological examination showed an increase in the number of melanocytesin the stratum basale with lined melanocytes. Based on histopathological examination in this patient moreleads to the diagnosis of PJS